Acoustic signalling during courtship in the painted goby, Pomatoschistus pictus - Amorim, Maria Clara Pessoa (2012)
Gobies emit sounds during different stages of reproduction, including courtship, pre-spawning events (in the nest) and spawning. The breeding sounds of the painted goby Pomatoschistus pictus and associated courtship behaviour were recorded in captivity and described for the first time. Males emitted thump-like sounds mainly when displaying alone in the nest and produced drumming sounds outside the nest. Thumps have never been reported for other species of the genus Pomatoschistus. Thumps were short (~80 ms) very-low frequency (below 100 Hz) non-pulsed sounds, whereas drums were longer (hundreds of ms) and consisted of low frequency (~300 Hz) pulse trains. Thump characteristics varied significantly among males but also showed high within-male variability. The frequency of thump emissions and courtship behaviour (total number of courtship displays, lead and nest display) were positively correlated with male size but not with male somatic condition. Thump bursts emitted during nest displays were significantly longer than when emitted with other behaviours. These results suggest that larger males courted females more intensively, both with visual and acoustic displays, than smaller ones.